Direct Interspecies Electron Transfer Mediated by Graphene Oxide-Based Materials - Igarashi, Kensuke; Miyako, Eijiro; Kato, Souichiro (Frontiers in Microbiology, 2020)
Conductive materials are known to promote direct interspecies electron transfer (DIET) by electrically bridging microbial cells. Previous studies have suggested that supplementation of graphene oxide (GO) based materials, including GO and reduced GO (rGO), to anaerobic microbial communities, can promote DIET. This promotion mechanism is thought to be involved in electron transfer via rGO or biologically formed rGO. However, concrete evidence that rGO directly promotes DIET is still lacking. Furthermore, the effects of the physicochemical properties of GO-based materials on DIET efficiency have not been elucidated. In the current work, we investigated whether chemically and biologically reduced GO compounds can promote DIET in a defined model coculture system, and also examined the effects of surface properties on DIET-promoting efficiency. Supplementation of GO to a defined DIET coculture composed of an ethanol-oxidizing electron producer Geobacter metallireducens and a methane-producing electron consumer Methanosarcina barkeri promoted methane production from ethanol. X-ray photoelectron spectroscopy revealed that GO was reduced to rGO during cultivation by G. metallireducens activity. The stoichiometry of methane production from ethanol and the isotope labeling experiments clearly showed that biologically reduced GO induced DIET-mediated syntrophic methanogenesis. We also assessed the DIET-promoting efficiency of chemically reduced GO and its derivatives, including hydrophilic amine-functionalized rGO (rGO-NH2) and hydrophobic octadecylamine-functionalized rGO (rGO-ODA). While all tested rGO derivatives induced DIET, the rGO derivatives with higher hydrophilicity showed higher DIET-promoting efficiency. Optical microscope observation revealed that microbial cells, in particular, G. metallireducens, more quickly adhered to more hydrophilic GO-based materials. The superior ability to recruit microbial cells is a critical feature of the higher DIET-promoting efficiency of the hydrophilic materials. This study demonstrates that biologically and chemically reduced GO can promote DIET-mediated syntrophic methanogenesis. Our results also suggested that the surface hydrophilicity (i.e., affinity toward microbial cells) is one of the important determinants of the DIET-promoting efficiencies. These observations will provide useful guidance for the selection of conductive particles for the improvement of methanogenesis in anaerobic digesters.